2021
DOI: 10.21521/mw.6597
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pregnancy protein levels to distinguish between singleton and twin pregnancies in Awassi sheep

Abstract: Determining the fetal number to avoid pregnant sheep management, feeding, and delivery issues is of vital importance. This study aimed to determine the levels of pregnancy-associated glycoprotein (PAG) and pregnancy-specific protein B (PSPB), which are pregnancy proteins, to accurately predict singleton and twin pregnancies in Awassi sheep. A total of 40 Awassi sheep were used for the study. According to the number of offspring, pregnant ewes were separated into two groups. The study's first group (Group 1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Although the serum PAGs profiles of the ewes having not been assessed for singleton and multiple pregnancies constitute a limitation for the present study, the reason for such a classification having not been made was to mimic the probable results expected to be achieved with the use of the bovine PAG‐ELISA test on the field for pregnancy diagnosis. Previous studies have reported that serum PAGs and PSPB levels determined with the RIA and sheep ELISA methods were higher in multiple pregnant ewes, compared to singleton pregnant ewes (Akkuş & Yaprakcı, 2022 ; El Amiri et al., 2014 , 2015 ; Ranilla et al., 1997 ). However, the differences observed in the serum PAGs levels of singleton and multiple pregnant ewes measured with bovine PAG‐ELISA pregnancy tests do not change the results of pregnancy diagnosis (Akköse et al., 2021 ; Alkan et al., 2020 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the serum PAGs profiles of the ewes having not been assessed for singleton and multiple pregnancies constitute a limitation for the present study, the reason for such a classification having not been made was to mimic the probable results expected to be achieved with the use of the bovine PAG‐ELISA test on the field for pregnancy diagnosis. Previous studies have reported that serum PAGs and PSPB levels determined with the RIA and sheep ELISA methods were higher in multiple pregnant ewes, compared to singleton pregnant ewes (Akkuş & Yaprakcı, 2022 ; El Amiri et al., 2014 , 2015 ; Ranilla et al., 1997 ). However, the differences observed in the serum PAGs levels of singleton and multiple pregnant ewes measured with bovine PAG‐ELISA pregnancy tests do not change the results of pregnancy diagnosis (Akköse et al., 2021 ; Alkan et al., 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…the Konya Merino(Uçar et al, 2018), Awassi(Akköse et al, 2021;Akkuş & Yaprakcı, 2022), Awassi X Merino crossbreed(Karen et al, 2003), German Blackheaded Mutton (GBM), Rhoen X GBM X Dorper crossbreed(Ledezma-Torres et al, 2006), Sarda X Lacaune crossbreed(De Carolis et al, 2020) and Corriedale and Ile de France X Texel crossbreed(Rovani et al, 2016), the serum PAG1 levels of the Polypay X Dorset crossbreed(Roberts et al, 2017) and the serum PSPB levels of the Awassi(Akkuş & Yaprakcı, 2022) and Yankasa(Adeyeye et al, 2021) with minor differences. The steady increase in the level of PAGs as pregnancy advances appears to be associated with increased PAGs production in the binucleate cells of the placenta.…”
mentioning
confidence: 99%